Leadership styles as a source of employee organizational identification - Alharbi, Khalid K.; Abdullah, Abdul Rashid (IJECM, 2016)
The notion that leadership styles could be a source for organizational identification have caught attention by human resource management and organizational behaviour scholars in recent years. Leadership is one of the most complex and widely studied construct in organizational studies. The purpose of this paper is to review the impact of leadership styles on employee organizational identification. Theoretical and empirical studies were reviewed and summarized. The review revealed that the general link of leadership-organizational identification has been widely accepted, and most studies focus on transformational leadership, while other leadership styles should be considered.